The Effect of Financial Performance on Firm Value: Good Corporate Governance as Moderating Variable - Bingar Violita Dwi Andayu (APSSAI, 2025)
Research aims: This study intends to examine how financial performance, assessed through ROA, DER, CR, and PE, impacts Firm value, with GCG and managerial ownership acting as a moderating factor, in technology firms within Indonesia. Design/Methodology/Approach: This research adopts a quantitative explanatory framework using secondary data derived from financial report documents of technology companies registered on the Indonesia Stock Exchange (IDX) for the period 2021–2023. From a total of 48 companies, 35 were selected using purposive sampling based on criteria such as regularly releasing audited financial statements. The study employed panel data with a pooled data method and was analyzed through Moderated Regression Analysis (MRA). Research findings: The findings indicate that ROA, DER, CR, and PER together affect Firm value. To some extent, ROA and DER significantly influence Firm value, whereas CR and PER do not. GCG, represented by managerial ownership, does not influence the connection between financial performance and firm value. Theoretical contribution/Originality: This study provides insights into the limited role of GCG in shaping the impact of financial performance on firm value, particularly in technology companies post-pandemic. Practitioner/Policy implication: The results indicate that corporate management ought to prioritize enhancing profitability and the efficiency of capital structure, while reassessing the strategic importance of managerial ownership in governance. Research limitation/implication: This research focuses on technology firms listed on the IDX from 2021 to 2023 and may not accurately represent conditions in different industries or periods.